Sustainable development from resource exploitation perspective - Abd. Rashid Ahmad; Hasnah Ali (Universiti Kebangsaan Malaysia, 1999)
Sustainable development denotes human desire to change (for better or worse) indefinitely without seriously affecting his environment. Although the physical systems of planet earth have the capacity to sustain life supporting processes for a long period of time through various biogeochemical cycles, interruptions of these processes by human development activities could cause impairment of the environment. A high rate of economic growth and development could cause depletion of resources, such as petroleum as one of the most important energy resources. There are opposing views on resource sustainability for development, the pessimistic, optimistic and moderate views. The basis of these views, is analysed. Resource exploitation and depletion by transnational corporations activities are also discussed. This paper attempts to review and analyse the relationship between man strive to achieve sustainable development and the earth capacity to sustain this strive. It also attempts to draw conclusions whether sustainable development is real or is just a dream that could turn into a nightmare.